Trends in area and production of vegetables, future projections in Romania - Cristina Maria Sterie (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
This study analyzes the state of vegetable cultivation and production in the European Union, with a focus on Romania. In 2022, Romania ranked 6th in the EU in terms of vegetable acreage but experienced a significant decline, and using SPSS, we forecast vegetable production and cultivation trends. Projections for 2030 suggest varying scenarios, reflecting the challenges and uncertainties in agriculture. This research underscores the need for innovation and sustainability to navigate the evolving agricultural landscape.
Keywords: Q1; Q13; 330; agriculture; vegetable; SPSS; Romania